The relationship between black fungus and Covid-19 disease in diabetes mellitus patients - Ataye, Ahmad Wali; Rustampoor, Mohammad Hussain; Sarwary, Matin; Zalmai, Saniullah; Qudratullah , Ibrahimi (Eximia, 2022)
Introduction: The emergence of the novel coronavirus disease (COVID-19) pandemic has conditioned the whole world to search for an ultimate cure for the infection. Therefore, all countries with no exception have embraced vaccines in addition to other pharmacological drugs. The consequences of the pandemic include material and human losses in all countries. Another emerging disease is a black fungus. The black fungus is a pathological phenomenon that arises as a result of exposure to mucormycosis. It is observed concurrently with recovery from the virus. The infection has symptoms and risks that do not reduce the risk of infection by COVID-19. Methods: Information was gathered from the review of the relevant literature obtained from various databases, such as Science Direct, Springer, PubMed, Google, and Google Scholar. Results: The relationship between diabetes, COVID-19, and mucous fungus is such that diabetes weakens the immune system which helps the COVID-19 virus. Conclusion: The decline of the immune system facilitates secondary infections such as the mucous fungus, especially in the recovery phase from the virus. Therefore, in this review, information about the new pandemic and its risks have been summarized.